2013
DOI: 10.1177/0884533613507455
|View full text |Cite|
|
Sign up to set email alerts
|

State of Nutrition Support Teams

Abstract: The incidence of malnutrition in hospitalized patients is relatively high (up to 55%) despite breakthroughs in nutrition support therapies. These patients have increased morbidity and mortality, extended hospital stays, and care that is associated with higher costs. These patients are often poorly managed due to inadequate nutrition assessment and poor medical knowledge and practice in the field of nutrition. Nutrition support teams (NSTs) are interdisciplinary support teams with specialty training in nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 37 publications
0
68
0
6
Order By: Relevance
“…[20,21] Unlike this misconception with formal NSTs causing increased costs with minimal benefits, many studies [22,23] actually showed that when a proper management is done by an NST, there are significant improvements in the nutritional status of patients and in clinical outcomes, and it even leads to reductions in the expenses for hospitals. [14] Based on these findings, NST intervention for critically ill patients with GI disease would be expected to reduce mortality and morbidity. Martin et al [24] performed a multicenter, cluster-randomized clinical trial that compared characteristics between patients from 7 control hospitals (n = 214) and 7 nutrition intervention hospitals (n = 248).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21] Unlike this misconception with formal NSTs causing increased costs with minimal benefits, many studies [22,23] actually showed that when a proper management is done by an NST, there are significant improvements in the nutritional status of patients and in clinical outcomes, and it even leads to reductions in the expenses for hospitals. [14] Based on these findings, NST intervention for critically ill patients with GI disease would be expected to reduce mortality and morbidity. Martin et al [24] performed a multicenter, cluster-randomized clinical trial that compared characteristics between patients from 7 control hospitals (n = 214) and 7 nutrition intervention hospitals (n = 248).…”
Section: Discussionmentioning
confidence: 99%
“…[19] Several studies have shown favorable effects of NS for patients who are at nutritional risk within the ICU. [6,7] According to the systemic review from DeLegge and Kelley, [14] many hospitals and other organizations in the healthcare field have been gradually reducing the number of NSTs lately even with their proven efficacy through literature, because they try to find ways to lower expenses. According to the 2008 survey by the American Society for Parenteral and Enteral Nutrition (ASPEN), only 42% of the respondents, who practice in a hospital setting, reported that they had official NSTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Aynı şekilde daha önce yapılan çalışmalarda hastaya özel PN desteği sağlayan KNÜ'nün bulunduğu multidisipliner merkezlerde, PN'nin etkinlik, gü-venirlilik ve kalitesinde kayda değer bir artışla beraber, malnütrisyon hastalarının hastanede kalış süresi, morbidite ve mortalite oranlarını düşürdüğü bildirilmektedir. [27][28][29][30][31][32][33] Yine, yapılan çalışmalarda BDE'lerin sıkı laboratuvar ve klinik monitorizasyona bağlı olarak elektrolit dengesizlikleri gibi metabolik komplikasyonları önemli ölçüde azalttığı, sepsis, pnömotoraks gibi kateterle ilişkili komplikasyonların, nütrisyon konusunda eğitimli bir takım ve/veya tecrübeli hekimlerle azalabilmekte olduğu ve klinik bakımın kalitesini artırarak maliyeti azalttığı; nütrisyon takımının önerilerinin mali avantajlar sağlayabileceği bildirilmiştir 4,5,[34][35][36][37][38][39] Bununla beraber, compounder sisteminin uygulanabilmesi için aseptik ortam şartı ve dolum işleminde görevli eğitimli personel şartı vardır. 40,41 Dolayısıyla ideal sonuçlar için günlük parenteral beslenen hasta sayısı çok önemlidir.…”
Section: Bulgularunclassified
“…NSTs typically comprise physicians, dietitians, nurses, laboratory medical technologists and pharmacists [1]. NST intervention usually includes nutritional assessment, determination of nutritional requirements, recommendations for appropriate nutrition therapy and management of nutrition support therapy.…”
Section: Introductionmentioning
confidence: 99%